The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7554/elife.62184
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for Cav1.4 Ca2+ channels in the molecular and structural organization of the rod photoreceptor synapse

Abstract: Synapses are fundamental information processing units that rely on voltage-gated Ca2+ (Cav) channels to trigger Ca2+-dependent neurotransmitter release. Cav channels also play Ca2+-independent roles in other biological contexts, but whether they do so in axon terminals is unknown. Here, we addressed this unknown with respect to the requirement for Cav1.4 L-type channels for the formation of rod photoreceptor synapses in the retina. Using a mouse strain expressing a non-conducting mutant form of Cav1.4, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 47 publications
(84 reference statements)
3
29
0
Order By: Relevance
“…Thus, they are in different positions and with different combinations of glutamate receptors within the area of glutamate spillover diffusion; GABA and ephaptic conduction are probably also involved here ( Kramer and Davenport, 2015 ; Petralia et al, 2017 ). The main invaginating structures extend from bipolar and horizontal cells; their invagination and function are partly dependent on trans-synaptic complexes of proteins including calcium channel subunits and receptors ( Kerschensteiner, 2017 ; Wang et al, 2017 ; Cao et al, 2020 ; Maddox et al, 2020 ; Tsukamoto et al, 2021 ). Invaginating horizontal cell processes form a type of reciprocal synapse including a feed-forward function along with negative feedback to provide lateral inhibition to help the brain modulate signals from groups of adjacent photoreceptor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are in different positions and with different combinations of glutamate receptors within the area of glutamate spillover diffusion; GABA and ephaptic conduction are probably also involved here ( Kramer and Davenport, 2015 ; Petralia et al, 2017 ). The main invaginating structures extend from bipolar and horizontal cells; their invagination and function are partly dependent on trans-synaptic complexes of proteins including calcium channel subunits and receptors ( Kerschensteiner, 2017 ; Wang et al, 2017 ; Cao et al, 2020 ; Maddox et al, 2020 ; Tsukamoto et al, 2021 ). Invaginating horizontal cell processes form a type of reciprocal synapse including a feed-forward function along with negative feedback to provide lateral inhibition to help the brain modulate signals from groups of adjacent photoreceptor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic differences in rod and cone phenotype have been found in different mouse models carrying mutations in the Ca V 1.4 channel complex. While some found that cones are spared 13 , 17 , 31 , 55 , 56 , other reported drastic changes compared to rods 14 , 27 . Still, a recent study showed that the Ca V 1.4.IT mutation can exert different functional phenotypes depending on splice variant and subunit composition 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Rod bipolar and horizontal cell neurites appose mature spherules in the OPL and ectopically in the ONL, but fail to invaginate into the spherules (Fig. 3C) (Maddox et al 2020). Although the cone phenotype of the G369i mice is still under investigation, these results suggest that while dispensable for the molecular organization of rod synapses, Cav1.4 Ca 2+ influx is required for their structural maturity and localization in the OPL.…”
Section: Cav14 Regulates the Maturation And Function Of Rod And Cone Synapsesmentioning
confidence: 90%
“…2A-C). A role for Cav1.4 in mediating presynaptic Ca 2+ signals in mouse photoreceptors is further supported by the near elimination of depolarization-evoked Ca 2+ transients in the OPL (Mansergh et al 2005, Regus-Leidig et al 2014 and the lack of rod ICa in Cav1.4 knockout (KO) mice (Maddox et al 2020). Cav1.4 protein is tightly clustered along the base of the synaptic ribbon in rods and cones (Liu et al 2013b, Morgans 2001, and thus is well-positioned to regulate the exocytosis of glutamate.…”
Section: Cav14 Regulates the Maturation And Function Of Rod And Cone Synapsesmentioning
confidence: 99%